Vegetative growth and foliar nutrient contents of peach on different clonal rootstocks - Sobierajski, Graciela da Rocha; Blain, Gabriel Constantino; Teixeira, Luiz Antonio Junqueira; Mayer, Newton Alex (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to evaluate the effect of 19 clonal rootstocks on the vegetative growth and foliar nutrient contents of the 'BRS Kampai' and 'BRS Rubimel' peach (Prunus persica) trees. In the period of 2014 to 2018, two field trials were carried out in the municipalities of Jarinu and Jundiaí, in the state of São Paulo, Brazil. The BRS Kampai and BRS Rubimel cultivars, budded on 19 clonal rootstocks, besides their own-rooted scions, were evaluated in Jarinu and Jundiaí, respectively. In Jarinu, the Barrier, Cadaman, 'Capdeboscq', Flordaguard, GxN9, I-67-52-4, 'Okinawa', México Fila-1, Nemared, Tsukuba-2, and Tsukuba-3 rootstocks, as well as the own-rooted scion, showed the best performance for vegetative growth and foliar nutrient contents. In Jundiaí, all genotypes, except Marianna 2624 and Mirabolano 29C, did not show any statistical difference regarding vegetative growth. The performance of own-rooted 'BRS Kampai' and 'BRS Rubimel' is similar to that of traditional rootstocks, such as 'Okinawa'. Therefore, the evaluated scion cultivars may be an interesting alternative for sites with suitable biotic and abiotic soil conditions.